Investigation of the Electromagnetic Shielding Effectiveness of Carded and Needle Bonded Nonwoven Fabrics Produced at Different Ratios with Conductive Steel Fibers - (:unkn) unknown (INDA, 2015)
The number of electrical and electronic devices in our daily life has increased. The devices produce electromagnetic waves which harm human and environments. In recent years, there has been an increasing interest in the reduction and control of electromagnetic waves. The paper focuses on shielding of electromagnetic waves of nonwoven fabrics produced with needle punching technology from conductive stainless steel fibers. The needle punched nonwoven fabrics were produced with carding and needle punching technology by blending stainless steel fibers and normal staple polyester fibers at different ratios for electromagnetic shielding applications. The electromagnetic shielding effectiveness of the nonwoven fabrics with conductive stainless steel fibers was tested. After blending of stainless steel fibers and normal polyester fibers, the webs were formed by a wool-type carding machine and the after web folding operation, the webs were bonded by needle punching at constant working parameters. During production, the needle punch densities per cm(2) and needle penetration depth per mm were kept constant. Bulky needle punched nonwoven fabrics with low needling density were produced. The main objective of our research was to develop the nonwoven fabric for shielding against electromagnetic waves. In addition, the effect of the stainless steel fiber ratio used in the needle punched nonwoven fabrics on electromagnetic shielding effectiveness was investigated. After production, the thicknesses of the needle punched nonwoven fabrics were tested. The electromagnetic shielding effectiveness, reflection and absorption values of the needle punched nonwoven fabric samples were measured at the frequency range of 15-3000MHz and presented in table and graphics. As the ratio of stainless steel fibers used in the nonwoven fabric increased, Electromagnetic shielding effectiveness values (EMSE) were increased in a linear manner and obtained results were discussed. It was found that the electromagnetic waves were shielded about 90% at high frequencies, 85% at medium frequencies, and 80% at low frequencies by needle punched nonwoven fabric with 5% conductive stainless steel fiber. The EMSE values such as 20dB, 25dB and 45dB were obtained at low frequency ranges (0-300MHz and 25dB, medium frequency ranges, 300-1200MHz and 45dB, and high frequency ranges, 1200-3000MHz) with the needle punched nonwoven fabric containing 25% conductive stainless steel fiber.
Keywords: nonwoven; stainless steel fiber (SSF); needle punched; electromagnetic shielding; needle punching; conductive textiles